What’s in it for me? Enlightening motivation within a social network decision-making - Antunes, Francisco (2013)
This paper addresses the motivations by which people engage in social networking, according to the existing literature. Understanding these motivations allows firms to set processes to explore them, in order to establish and develop a decision support social network, supported by social network sites. Participating in social networks draws upon the interaction of intrinsic and extrinsic factors. On one hand, intrinsic factors refer to motivation embedded in the action itself (comes within the individual), rather than from external rewards such as money or recognition. On the other hand, extrinsic factors refer to the motivation coming outside the individual. Considering that solutions to problems are expected within a decision support social network, some potential problems are identified and addressed.